2007
DOI: 10.1271/bbb.60716
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Growth Inhibition and Differentiation of Human Leukemia HL-60 Cells by a Tunisian Gerboui Olive Leaf Extract

Abstract: Cancer protection associated with the consumption of olive products is well established, but not for leukemia. The protective effects of olive (Olea europaea L.) leaves were investigated by incubating human promyelocytic leukemia HL-60 cells with olive leaf extracts (OLEs) from seven principal Tunisian olive varieties, namely, Chemchali, Chemlali, Chétoui, Gerboui, Sayali, Zalmati and Zarrazi. The results showed significant growth inhibition of HL-60 cells incubated for 48 h with a 100-fold dilution of each OL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 26 publications
3
55
1
2
Order By: Relevance
“…Despite the fact that previous research has already tested the anti-proliferative and/or cell killing abilities of different olive leaf extracts against leukemia cells (Abaza et al, 2007;Fares et al, 2011;Samet et al, 2014), none of them has proved whether the extracts maintained their anticancer properties once they entered the gastrointestinal tract. Therefore, olive leaf extracts warrant further investigation into their potential antileukemic benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that previous research has already tested the anti-proliferative and/or cell killing abilities of different olive leaf extracts against leukemia cells (Abaza et al, 2007;Fares et al, 2011;Samet et al, 2014), none of them has proved whether the extracts maintained their anticancer properties once they entered the gastrointestinal tract. Therefore, olive leaf extracts warrant further investigation into their potential antileukemic benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that olive leaf extract exhibits a large spectrum of in vitro and in vivo properties, including antioxidant activity [85,86], radio-protective effects [85], anti-proliferative effect on leukemia cells by inducing apoptosis [39,57,87,88], cytotoxic activity against human breast cancer cells [47,89], anti-HIV virus effect [90], antifungal activity [91], gastroprotective activities [92], attenuation of diabetic neuropathic pain [93] and amelioration of gentamicin nephrotoxicity [94]. Several biological properties such as antioxidant, anti-atherosclerotic, hypoglycemic and cardioprotective effects of olive leaves have been reviewed in the literature [76,82].…”
Section: Benefits Of Olive Leavesmentioning
confidence: 99%
“…Morphological assessment of differentiation was evaluated by Wright-Giemsa staining. 23 The percentage of cells capable of reducing nitro blue tetrazolium (NBT) was measured as described earlier in Abaza et al 24 The results were determined by examining 200 cells per microscopic field and counting 5 times in each group. The data were expressed as the percentage of blue cells per (blue 1 white cells).…”
Section: Cell Cycle and Differentiation Analysesmentioning
confidence: 99%